Personal Habit and Carcinoma of Larynx, Hypopharynx among Bangladeshi lower socio-economic group of people: An Observational Study (The Journal of Ad-din Women's Medical College, 2023)
Background: Personal habits like, tobacco consumption through smoking and oral intake is one of the most important risk factor of laryngeal and hypopharyngeal cancers among the low socioeconomic group of people. Developing countries like ours face arduous challenge to provide adequate treatment facilities from its poor resource settings to these patients. Constant evaluation of theses cancer patients in regard to their exposure to the hazardous personal habits can portray the current situation, thus can find out the scopes of implementation of necessary control measures and awareness build up actions.Objective: The present study observed tobacco consumption and other personal habits in patients with laryngeal or hypopharyngeal cancers.Methods: This is an descriptive type of cross sectional study, where 100 patients with laryngeal or hypopharyngeal cancers have been assessed, from two of the tertiary care hospital in Dhaka division, during the period of 2018 to 2021. Face to face interview was performed and medical records have been checked to collect data.Result: In the present study, 65 patients were suffering from carcinoma of larynx and 35 patients were suffering from carcinoma of hypopharynx. Carcinoma in the supra-glottic region was evident in 53.0% cases, glottic and subglottic carcinoma were 11.0% and 1.0% respectively. Carcinoma in the pyriform fossa was 29.0% and post-cricoid carcinoma was 6.0%. With the age range of 35 to 75 years, laryngeal carcinoma was highest observed in the age group of 46 to 55 years (26 out of 65 cases) and hypopharyngeal carcinoma was highest observed in the age group of 35 to 45 years (11 out of 35 cases). In 83.0% cases, the respondents were illiterate and in 80.0% cases they were residents of rural area. More than half of the respondents were farmers (57.0%). The monthly income range of the respondents was 2000-12000 BDT and 50.0% of the respondents belonged from the lower quartile of this income range. Among the patients, 99 of them were tobacco consumers where, 93 of them were smokers and 38 of them were oral tobacco leaf consumers; 33 patients recorded to be consumers of tobacco leaf along with smoking.Conclusion: With this high prevalence of smoking among the laryngeal and hypopharyngeal cancer patients, it can be estimated that, the lower socio economic group of people are at high risk of cancer in the oral region which can increase the overall cancer related morbidity and mortality in our country. Thus, findings from this study urges for strict control and monitoring measures on availability of tobacco products, as well as, necessitates awareness build up actions regarding the harmful health effects of tobacco among the lower socioeconomic group of people.The Journal of Ad-din Women's Medical College; Vol. 10 (2), July 2022; p 15-20